Method for preparing alkaline fuel cell catalyst layer containing high water retention and high ion conductivity additive and use thereof

By introducing additives with high water retention and high ion conductivity into alkaline fuel cell catalysts, the problem of excessively dry cathode catalyst layers was solved, improving catalyst utilization and ion transport capacity, and enhancing fuel cell performance.

CN117936807BActive Publication Date: 2026-11-06INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311547247.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2026-11-06
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

In alkaline fuel cells, an excessively dry cathode catalyst layer leads to low catalyst utilization, high ion transport resistance, and poor catalytic performance.

Method used

Introducing additives with high water retention and high ion conductivity into the catalyst creates additional ion transport channels, enhances the ion transport capacity of the three-phase contact interface, and provides a more water environment for the cathode catalyst layer, thereby improving the mass transfer process.

Benefits of technology

It significantly improves catalyst utilization and ion transport capacity, thereby enhancing the performance of alkaline fuel cells, particularly peak power density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117936807B_ABST
    Figure CN117936807B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of fuel cells, in particular to an alkaline fuel cell catalyst containing a high-water-retention and high-ion-conductivity additive, a preparation method and application, and the alkaline fuel cell catalyst containing the high-water-retention and high-ion-conductivity additive, which comprises an unmodified catalyst and an additive, the unmodified catalyst is an alkaline fuel cell catalyst, the additive is an organic substance with high water retention and high ion conductivity, and the additive is adsorbed on the unmodified catalyst. The application overcomes the problems of low catalyst utilization, high ion transmission resistance and poor catalytic effect caused by the over-dryness of a cathode catalyst layer in an existing alkaline fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fuel cell technology, and in particular to alkaline fuel cell catalysts containing additives with high water retention and high ion conductivity, their preparation methods, and applications. Background Technology

[0002] Fuel cells are clean and efficient energy conversion devices. In particular, alkaline ion-exchange membrane fuel cells (AEMFCs) are considered one of the most promising energy devices due to their high energy density, high output power, zero pollution, and the likelihood of using non-precious metal materials as catalysts. As the "heart" of an AEMFC, the membrane electrode assembly (MEA) mainly consists of a gas diffusion layer, a catalyst layer, and a polyelectrolyte membrane. Among these, the catalyst layer, where the catalytic reaction occurs, plays a crucial role in the performance of the MEA.

[0003] The catalyst layer of an alkaline fuel cell is composed of catalyst particles and ionomers. The ionomers act as binders and ionic conductors, interacting with the catalyst to form a complete three-phase interface for ions, electrons, and reactants. To achieve higher power density fuel cell performance, a more efficient three-phase transport interface is required to accelerate the reaction. However, in practice, alkaline fuel cells often experience flooding of the anode catalyst layer and excessive dryness of the cathode catalyst layer during operation. Excessive dryness of the cathode catalyst layer further obstructs the three-phase transport interface within the catalyst layer, reducing catalyst utilization and thus affecting the performance of the alkaline fuel cell.

[0004] Currently, most improvements to address the problem of excessively dry cathodes within the catalyst layer of alkaline ion exchange membrane fuel cells focus on modifying the ionomer structure. Adjusting the ionomer structure enhances water retention and ion conductivity. However, increasing the water retention of the ionomer reduces its adhesive strength and mechanical strength, which negatively impacts the stability of alkaline fuel cells. Therefore, improving water retention and ion conductivity through ionomer structure modification has limitations. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity, as well as its preparation method and application, to overcome the problems of low catalyst utilization, high ion transport resistance and poor catalytic effect caused by the excessively dry cathode catalyst layer in existing alkaline fuel cells.

[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0007] This invention improves the performance of alkaline fuel cells by introducing additives with both high water retention and high ion conductivity into the catalyst. Specifically, the additives introduced into the cathode catalyst form additional ion transport channels in the catalyst structure, further enhancing the ion transport capacity at the three-phase interface and effectively solving the demanding design requirements of the three-phase interface in the catalyst layer. At the same time, the introduced additives have high water retention properties, providing more water environment for the cathode catalyst layer to accelerate the mass transfer process and further improve the utilization rate of the catalyst.

[0008] Methods for preparing alkaline fuel cell catalysts containing additives with high water retention and high ion conductivity include direct additive introduction or additive coating.

[0009] The additive direct introduction method is prepared according to the following steps: the unmodified catalyst and additive are dispersed in solvent I, stirred and mixed at 25-80℃ for 1-72h, and then separated and dried by centrifugation or vacuum filtration to obtain an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity.

[0010] The additive coating method is prepared according to the following steps: the unmodified catalyst is mixed evenly with the alkaline ionomer and then dispersed in solvent II to obtain a catalyst-ionomer dispersion. The catalyst-ionomer dispersion is coated to obtain a catalyst layer. Then, the additive is coated and penetrated into the catalyst layer to obtain an alkaline fuel cell catalyst layer containing additives with high water retention and high ion conductivity.

[0011] The coating methods are independently selected from spraying, printing or roller coating to obtain an alkaline fuel cell catalyst layer containing additives with high water retention and high ion conductivity.

[0012] Preferably, solvent I is selected from water, methanol, ethanol, propanol, isopropanol, ethylene glycol, glycerol, acetone, chloroform, N,N , -One or more combinations of dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone;

[0013] In the direct additive introduction method, the mass ratio of the unmodified catalyst to the additive is 1:0.01-10, and the mass ratio of the unmodified catalyst to the basic ionomer is 0.1-10:1.

[0014] The alkaline ionomer is selected from one of FAA-3-SOLUT-10, FAA-3-EtOH-5, PiperION-A5-HCO3-EtOH, Pention-D35-5wt%, Pention-D18-5wt%, Pention-S72-10wt%, Pention-S72-20wt%, Pention-S72-5wt%, SustainionXA-9, SustainionXB-7XC-1, and SustainionXC-2.

[0015] Solvent II is H2O, isopropanol, or a mixture of both.

[0016] Preferably, the additive is selected from one or more combinations of tetramethylammonium, tetramethylammonium-R (a tetramethylammonium derivative), mepiquat chloride, mepiquat chloride-R (a mepiquat chloride derivative), halmanine, halmanine-R (a halmanine derivative), trigonelline, trigonelline-R (a trigonelline derivative), 5,10,15,20-tetra(4-trimethylamino)phenylporphyrin tetratoluenesulfonate, and polyacrylamide;

[0017] Wherein, R is selected from one or more combinations of methyl, ethyl, propyl, butyl, carboxyl, carbonyl, ether, phenyl, and amino.

[0018] Preferably, the derivatives of the tetramethylammonium hydroxide include tetraethylammonium hydroxide, triethylmethylammonium hydroxide, trimethylphenylammonium hydroxide, N,N,N-trimethyl-1-adamantylammonium hydroxide, and benzyltrimethylammonium hydroxide; the derivatives of the halman base include 1-methyl-9H-pyrido[3,4-b]indole-6-amino, methyl 6-amino-1-methyl-9H-pyrido[3,4-b]indole-3-carboxylic acid, halphenol, and picolinate. Arecoline, 1-methyl-1,2,3,4-tetrahydro-β-carboxylic acid; the derivatives of the trigonelline include arecoline, 1-methyl-3,6-dihydro-2H-pyridine-5-carboxylic acid prop-2-ynyl ester, guanidine ethyl ester, N,N-diethyl-1-methyl-3,6-dihydro-2H-pyridine-5-carboxamide, 1-methyl-1,2,5,6-tetrahydronicotinic acid ethyl ester, arecoline, and 1-methyl-4-oxopiridine-3-carboxylic acid ethyl ester.

[0019] Preferably, the unmodified catalyst is selected from one or more combinations of commercial Pt-C catalysts, noble metal alloy catalysts, noble metal single-atom catalysts, non-noble metal single-atom catalysts, and non-noble metal alloy catalysts.

[0020] Preferably, the commercial Pt-C catalyst is selected from: JM20% Pt-C, JM40% Pt-C, TKK46.5% Pt-C; the noble metal alloy catalyst is selected from TKK47% PtCo-C, JM PtRu-C; the noble metal single-atom catalyst is selected from Pt-NC, Pd-NC, Ir-NC; the non-noble metal single-atom catalyst is selected from Fe-NC, Co-NC, Ni-NC, Mn-NC, FeCo-NC, FeMn-NC, Fe-Ni-NC; and the non-noble metal alloy catalyst is selected from FeCo-C, FeNi-C.

[0021] The present invention also protects the alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity prepared by the above preparation method, comprising an unmodified catalyst and additives, wherein the unmodified catalyst is an alkaline fuel cell catalyst, and the additives are organic compounds with high water retention and high ion conductivity, and the additives are adsorbed on the unmodified catalyst.

[0022] This invention also protects the preparation of a cathode catalyst layer using an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity. The alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity, prepared by the direct introduction of additives, is used as the raw material. The cathode catalyst layer is prepared according to the following steps: the alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity is mixed evenly with an alkaline ionomer, and then dispersed in solvent II to obtain a catalyst-ionomer dispersion. The catalyst-ionomer dispersion is then uniformly coated onto an alkaline membrane to obtain the cathode catalyst layer.

[0023] In the additive coating method, the mass ratio of alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity to alkaline ionomer is 0.1-10:1;

[0024] Using an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity prepared by an additive coating method as raw material, the cathode catalyst layer is prepared according to the following steps: the unmodified catalyst is mixed evenly with an alkaline ionomer, and then dispersed in solvent II to obtain a catalyst-ionomer dispersion. The catalyst-ionomer dispersion is coated onto an alkaline membrane to obtain a catalyst layer. Then, additives are coated and permeated into the catalyst layer to obtain an alkaline fuel cell catalyst layer containing additives with high water retention and high ion conductivity.

[0025] The alkaline membrane is selected from one of the following: Xion-petion-72-15CL-10, Xion-petion-72-5CL-10, Xion-petion-20, Xion-petion-30, Xion-petion-50, PiperION-A15R-HC03, PiperION-A20R-HC03, PiperION-A40R-HC03, FAA-3-20, FAA-3-50, FAA-3-PE-30, FAA-3-PK-75, Sustainion B28-50 Grade T, Sustainion X37-50 Grade 60, W-25, and W-15.

[0026] The coating methods for the direct introduction of additives and the coating of additives are independently selected from spraying, printing or roller coating.

[0027] This invention also protects the application of the cathode catalyst layer in the preparation of an alkaline fuel cell, which is prepared according to the following steps:

[0028] An anode catalyst is coated on the anode side of an alkaline membrane coated with a cathode catalyst layer to form an anode catalyst layer. The alkaline membrane containing both the cathode and anode catalyst layers undergoes ion exchange in a KOH solution. During the ion exchange process, additives adhere to the catalyst layer. The ion-exchanged anion membrane is then directly used for alkaline fuel cell testing. The ion-exchanged alkaline membrane and a gas diffusion layer are then used together to form a membrane electrode assembly (MEA). At this point, the ion-exchanged alkaline membrane is sandwiched between two gas diffusion layers to form the MEA. The MEA is then assembled into a fuel cell fixture, and hydrogen is introduced into the anode and oxygen into the cathode.

[0029] Preferably, the anode catalyst layer is also coated with an additive, which may or may not be sprayed.

[0030] The anode catalyst includes one or more combinations of noble metal catalysts, non-noble metal catalysts, metal alloy catalysts, and metal oxide catalysts; the noble metal catalysts include Pt / C, Pd / C, and Ru / C; the non-noble metal catalysts include Fe / N / C, Co / N / C, Ni / N / C, Cu / N / C, and Zn / N / C; the metal alloy catalysts include PtRu-C, PdRu-C, RuFe-C, and PtNi-C; and the metal oxide catalysts include MoO2 and CeO2.

[0031] The gas diffusion layer is selected from one of carbon paper, carbon cloth, and graphite felt;

[0032] The concentration of KOH solution is 0.1-10 mol / L, and the ion exchange time is 3-150 h.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0034] (1) This invention directly modifies the catalyst or catalyst layer by adsorbing an additive with ion-conducting capabilities onto the catalyst surface, thereby providing more channels for ion transport within the catalyst layer. These ion transport channels can synergistically interact with alkaline ionomers to enhance the ion transport capacity in alkaline fuel cells.

[0035] (2) The additives selected in this invention also have high water retention capacity, which can retain a sufficient water environment in the catalyst layer and improve the ion transport capacity of the three-phase contact interface.

[0036] (3) In this invention, an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity is used in an alkaline fuel cell to form a cathode catalyst layer. In the alkaline fuel cell, the additives with high water retention and high ion conductivity provide additional ion transport channels and at the same time retain sufficient water environment for the catalyst layer, so that the overall activity of the modified catalyst is significantly improved relative to the catalyst itself. Attached Figure Description

[0037] Figure 1 These are schematic diagrams of the structures of tetramethylammonium hydroxide and its derivatives in Examples 1-6 of the present invention;

[0038] Figure 2 This is a schematic diagram of the catalyst structure formed by the interaction between the additives, unmodified catalysts and basic ionomers in Examples 1-6 of the present invention;

[0039] Figure 3 The left figure is a schematic diagram of the preparation process of the alkaline fuel cell catalyst layer prepared by the direct introduction of additives in Examples 1-14 and Example 24 of the present invention; the right figure is a schematic diagram of the preparation process of the alkaline fuel cell catalyst layer prepared by the additive coating method in Examples 15-23 of the present invention.

[0040] Figure 4 The diagram shows the Pt-C + tetramethylammonium hydroxide of Example 1 of this invention, and the effect of Pt-C in alkaline fuel cells.

[0041] Figure 5 These are schematic diagrams of the structures of mepiquat chloride in Example 7 and N-benzylalkylpyridinium in Example 8 of the present invention.

[0042] Figure 6 The images show the effects of PtCo-C + mepiquat chloride in Example 7, PtCo-C + N-benzylalkylpyridinium in Example 8, and the application of PtCo-C in alkaline fuel cells.

[0043] Figure 7 The structural schematic diagrams of Halman alkaloids and their derivatives in Examples 9-14 of this invention are shown below;

[0044] Figure 8 The diagram shows the application effects of Pt-N-C+Halman base and Pt-NC in alkaline fuel cells in Example 9 of this invention.

[0045] Figure 9 These are schematic diagrams of the structures of trigonelline and its derivatives in Examples 15-22 of this invention.

[0046] Figure 10 The diagram shows the application effects of Fe-N-C+ cucurbita alkali and Fe-NC in alkaline fuel cells in Example 15 of this invention.

[0047] Figure 11 The chemical structure diagram of 5,10,15,20-tetra(4-trimethylamino)phenylporphyrin tetramethylbenzenesulfonate of Example 23 of the present invention is shown.

[0048] Figure 12 The diagram shows the application effect of FeCo-C+5,10,15,20-tetra(4-trimethylamino)phenylporphyrin tetratoluenesulfonate and FeCo-C in alkaline fuel cells, as described in Example 23 of this invention.

[0049] Figure 13 The chemical structure diagram of the polyacrylamide in Example 24 of this invention is shown.

[0050] Figure 14 The diagram shows the application effect of Pt-C+Fe-NC-polyacrylamide in alkaline fuel cells according to Example 24 of the present invention. Detailed Implementation

[0051] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.

[0052] In this application, FeCo-C was prepared according to the method of Reduced Graphene Oxide-Supported Iron-Cobalt Alloys as High-Performance Catalysts for Oxygen Reduction Reaction;

[0053] In this application, FeNi-C is prepared according to the method of Graphicitic-shell encapsulated FeNi alloy / nitride nanocrystals on biomass-derived N-doped carbon as an efficient electrocatalyst for rechargeable Zn-air battery;

[0054] In this application, Pt-NC, Pd-NC, and Ir-NC are prepared according to Sequential Synthesis and Active-SiteCoordination Principle of Precious Metal Single-Atom Catalysts for OxygenReduction Reaction and PEM Fuel Cells;

[0055] In this application, FeCo-NC, FeMn-NC, and FeNi-NC are prepared according to the method of Transition metal and nitrogen-doped mesoporous carbons as cathode catalysts for anion-exchange membrane fuel cells;

[0056] In this application, Fe-NC, Co-NC, Ni-NC, and Mn-NC are prepared according to the method of Transition metal (Fe,Co,Mn,Cu) containing nitrogen-doped porous carbon as efficient oxygen reduction electrocatalysts for anion exchange membrane fuel cells;

[0057] Example 1

[0058] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0059] 10 mg of JM Pt-C catalyst (Pt mass fraction of 20 wt%) was mixed with 5 mg of tetramethylammonium hydroxide and dispersed in 10 mL of methanol solution. The mixture was stirred continuously for 24 h at 80 °C under a nitrogen atmosphere to obtain a suspension. The suspension was centrifuged and washed with methanol and aqueous solution to obtain an alkaline fuel cell catalyst sample, denoted as Pt-C+tetramethylammonium hydroxide. The sample was dried at 60 °C for 24 h.

[0060] Example 2

[0061] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0062] 10 mg of JM Pt-C catalyst (Pt mass fraction of 20 wt%) was mixed with 5 mg of tetramethylammonium hydroxide derivative (tetraethylammonium hydroxide) and dispersed together in 10 mL of methanol solution. The mixture was stirred continuously for 24 h at 80 °C under a nitrogen atmosphere to obtain a suspension. The suspension was centrifuged and washed with methanol and aqueous solution to obtain an alkaline fuel cell catalyst sample. The sample was dried at 60 °C for 24 h.

[0063] Example 3

[0064] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0065] 10 mg of JM Pt-C catalyst (Pt mass fraction of 20 wt%) was mixed with 5 mg of tetramethylammonium hydroxide derivative (triethylmethylammonium hydroxide) and dispersed together in 10 mL of methanol solution. The mixture was stirred continuously for 24 h at 80 °C under a nitrogen atmosphere to obtain a suspension. The suspension was centrifuged and washed with methanol and aqueous solution to obtain an alkaline fuel cell catalyst sample. The sample was dried at 60 °C for 24 h.

[0066] Example 4

[0067] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0068] 10 mg of JM Pt-C catalyst (Pt mass fraction of 20 wt%) was mixed with 5 mg of tetramethylammonium hydroxide derivative (trimethylphenylammonium hydroxide) and dispersed together in 10 mL of methanol solution. The mixture was stirred continuously for 24 h at 80 °C under a nitrogen atmosphere to obtain a suspension. The suspension was centrifuged and washed with methanol and aqueous solution to obtain an alkaline fuel cell catalyst sample. The sample was dried at 60 °C for 24 h.

[0069] Example 5

[0070] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0071] 10 mg of JM Pt-C catalyst (Pt mass fraction of 20 wt%) was mixed with 5 mg of tetramethylammonium hydroxide derivative (N,N,N-trimethyl-1-adamantylammonium hydroxide) and dispersed together in 10 mL of methanol solution. The mixture was stirred continuously for 24 h at 80 °C under a nitrogen atmosphere to obtain a suspension. The suspension was centrifuged and washed with methanol and aqueous solution to obtain an alkaline fuel cell catalyst sample. The sample was dried at 60 °C for 24 h.

[0072] Example 6

[0073] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0074] 10 mg of JM Pt-C catalyst (Pt mass fraction of 20 wt%) was mixed with 5 mg of tetramethylammonium hydroxide derivative (benzyltrimethylammonium hydroxide) and dispersed together in 10 mL of methanol solution. The mixture was stirred continuously for 24 h at 80 °C under a nitrogen atmosphere to obtain a suspension. The suspension was centrifuged and washed with methanol and aqueous solution to obtain an alkaline fuel cell catalyst sample. The sample was dried at 60 °C for 24 h.

[0075] The chemical structures of tetramethylammonium hydroxide and its related derivatives are as follows: Figure 1 As shown, to illustrate in detail the interaction between the selected additives (tetramethylammonium hydroxide and its derivatives) and the catalyst itself, a schematic diagram of the resulting catalyst structure is shown below. Figure 2 As shown, the additive tetramethylammonium hydroxide is uniformly adsorbed on the surface of the unmodified catalyst. In the alkaline fuel cell catalyst layer containing additives with high water retention and high ion conductivity, it works together with alkaline ionomers at the three-phase contact interface of the catalyst.

[0076] The catalysts Pt-C+tetramethylammonium hydroxide, Pt-C+tetraethylammonium hydroxide, Pt-C+triethylmethylammonium hydroxide, Pt-C+trimethylphenylammonium hydroxide, Pt-C+N,N,N-trimethyl-1-adamantylammonium hydroxide, and Pt-C+benzyltrimethylammonium hydroxide obtained in Examples 1-6 were mixed uniformly with an alkaline ionomer (FAA-3-SOLUT-10) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio 1:1) to obtain a coating solution. The coating solution was uniformly sprayed onto an alkaline membrane (FAA-3-20) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer; the alkaline anion membrane with the catalyst was subjected to ion exchange in a 1 mol / L KOH solution for 24 h. Figure 3 This is a schematic diagram of the alkaline membrane structure obtained by the direct additive introduction method after ion exchange. The alkaline membrane after ion exchange and the gas diffusion layer (carbon paper, 22BB) together constitute the membrane electrode assembly (MEA). The MEA was assembled into a fuel cell fixture for alkaline fuel cell testing. Hydrogen gas was introduced at the anode and oxygen gas at the cathode. The performance of two fuel cells composed of Pt-C and Pt-C-tetramethylammonium hydroxide was compared. The results show that the fuel cell composed of Pt-C-tetramethylammonium hydroxide has significantly improved performance compared to the fuel cell composed of Pt-C, with a peak power increase of 95 mW / cm². -2 , Figure 4 This paper demonstrates the effect of tetramethylammonium hydroxide (TMH) from Example 1 as an additive with high water retention and high ion conductivity on improving catalyst performance. Table 1 compares the degree to which different TMH derivatives, as water-retaining agents, improve the output power density of fuel cells.

[0077] Table 1. Performance of fuel cells with different water-retaining agents (tetramethylammonium hydroxide derivatives)

[0078]

[0079] Example 7

[0080] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0081] 10 mg of TKK PtCo-C catalyst (Pt mass fraction of 47 wt%) and 10 mg of mepiquat chloride were co-dispersed in 50 mL of ethanol solution and stirred continuously for 24 h in N2 atmosphere at 80 °C to obtain a suspension. The suspension was centrifuged and washed with ethanol and aqueous solution to obtain an alkaline fuel cell catalyst sample, denoted as PtCo-C+mepiquat chloride. The sample was dried at 60 °C for 24 h.

[0082] Example 8

[0083] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0084] 10 mg of TKK PtCo-C catalyst (Pt mass fraction of 47 wt%) and 10 mg of N-benzyl-N-methylpiperidinium were co-dispersed in 50 mL of ethanol solution and stirred continuously for 24 h in N2 atmosphere at 80 °C to obtain a suspension. The suspension was centrifuged and washed with ethanol and aqueous solution to obtain an alkaline fuel cell catalyst sample, denoted as PtCo-C+N-benzyl-N-methylpiperidinium. The sample was dried at 60 °C for 24 h.

[0085] The chemical structure diagrams of mepiquat chloride and N-benzyl-N-methylpiperidinium are shown below. Figure 5 As shown. The catalysts PtCo-C-mepiride and PtCo-CN-benzyl-N-methylpiperidinium obtained in Examples 7-8 were mixed evenly with an alkaline ionomer (Pention-D35-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio of 2:1) to obtain a coating solution. The coating solution was uniformly sprayed onto the alkaline membrane Xion-petion-72-15CL-10 to form the cathode catalyst layer; a commercial Ru-C catalyst was sprayed onto the anode side of the alkaline membrane to form the anode catalyst layer; the alkaline anion membrane sprayed with the catalyst was subjected to ion exchange in 0.5mol / L KOH solution for 48h, and the alkaline membrane after ion exchange and the gas diffusion layer (carbon paper, 22BB) together formed the membrane electrode. Membrane electrode assembly was used in a fuel cell fixture for alkaline fuel cell testing. Hydrogen was introduced into the anode and oxygen into the cathode. The performance of cells composed of PtCo-C, PtCo-C-mepirideamine, and PtCo-CN-benzyl-N-methylpiperidinium was compared. Figure 6 The study demonstrated the performance-enhancing effects of mepiquat chloride and N-benzyl-N-methylpiperidinium as high water-retention additives on fuel cells. Specifically, mepiquat chloride, as a high water-retention additive, increased the peak power density of the fuel cell by 250 mW / cm³. 2 N-Benzyl-N-methylpiperidinium, as a high water-retention additive, increased the peak power density of fuel cells by 300 mW / cm³. 2 .

[0086] Example 9

[0087] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0088] 10 mg of Pt-NC single-atom catalyst and 20 mg of Halman base were co-dispersed in 50 mL of DMSO and stirred continuously for 24 h in an N2 atmosphere at 80 °C to obtain a suspension. The suspension was centrifuged and washed with ethanol and aqueous solution to obtain an alkaline fuel cell catalyst, denoted as Pt-N-C+Halman base. The sample was dried at 60 °C for 24 h.

[0089] Example 10

[0090] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0091] 10 mg of Pt-NC single-atom catalyst and 20 mg of Halman base derivative (1-methyl-9H-pyrido[3,4-b]indole-6-amino) were co-dispersed in 50 mL of DMSO and stirred continuously for 24 h in a N2 atmosphere at 80 °C to obtain a suspension. The suspension was centrifuged and washed with ethanol and aqueous solution to obtain an alkaline fuel cell catalyst. The sample was dried at 60 °C for 24 h.

[0092] Example 11

[0093] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0094] 10 mg of Pt-NC single-atom catalyst and 20 mg of Halman base derivative (methyl 6-amino-1-methyl-9H-pyrido[3,4-b]indole-3-carboxylic acid) were co-dispersed in 50 mL of DMSO and stirred continuously for 24 h in a N2 atmosphere at 80 °C to obtain a suspension. The suspension was centrifuged and washed with ethanol and aqueous solution to obtain an alkaline fuel cell catalyst. The sample was dried at 60 °C for 24 h.

[0095] Example 12

[0096] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0097] 10 mg of Pt-NC single-atom catalyst and 20 mg of Halman base derivative (halphenol) were co-dispersed in 50 mL of DMSO and stirred continuously for 24 h in an N2 atmosphere at 80 °C to obtain a suspension. The suspension was centrifuged and washed with ethanol and aqueous solution to obtain an alkaline fuel cell catalyst. The sample was dried at 60 °C for 24 h.

[0098] Example 13

[0099] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0100] 10 mg of Pt-NC single-atom catalyst and 20 mg of Halman alkali derivative (quassin) were co-dispersed in 50 mL of DMSO and stirred continuously for 24 h in an N2 atmosphere at 80 °C to obtain a suspension. The suspension was centrifuged and washed with ethanol and aqueous solution to obtain an alkaline fuel cell catalyst. The sample was dried at 60 °C for 24 h.

[0101] Example 14

[0102] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0103] 10 mg of Pt-NC single-atom catalyst and 20 mg of Halman base derivative (1-methyl-1,2,3,4-tetrahydro-β-carboxylic acid) were co-dispersed in 50 mL of DMSO and stirred continuously for 24 h at 80 °C under N2 atmosphere to obtain a suspension. The suspension was centrifuged and washed with ethanol and aqueous solution to obtain an alkaline fuel cell catalyst. The sample was dried at 60 °C for 24 h.

[0104] Chemical structural diagrams of Halman alkaloids and their derivatives are shown below. Figure 7 As shown, the catalysts obtained in Examples 9-14 were mixed and uniformly dispersed with an alkaline ionomer (PiperION-A5-HCO3-EtOH) in solvent II of H2O and IPA (H2O to IPA volume ratio of 3:1) to obtain a coating solution. The coating solution was uniformly sprayed onto an alkaline membrane (PiperION-A40R-HC03) to form a cathode catalyst layer; Ru-Fe catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer; the alkaline anion membrane with the catalyst was subjected to ion exchange in a 5 mol / L KOH solution for 2 hours. The ion-exchanged alkaline membrane and the gas diffusion layer (carbon cloth) together formed a membrane electrode assembly (MEA). The MEA was assembled into a fuel cell fixture for alkaline fuel cell testing. Hydrogen gas was introduced at the anode and oxygen gas at the cathode. The performance of cells composed of Pt-NC, Pt-NC-Halman base, and other derivatives was compared and tested. Figure 8 The results of Example 9 demonstrate the performance-enhancing effect of Halman base as a high-water-retention additive on the fuel cell, increasing the peak power density of the fuel cell by 120 mW / cm³. 2 Table 2 compares the degree to which various Halman base derivatives, as water-retaining agents, improve the output power density of fuel cells.

[0105] Table 2 Performance of fuel cells with different water-retaining agents (halman alkali derivatives)

[0106]

[0107] Example 15

[0108] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0109] 50 mg of Fe-NC catalyst was uniformly mixed with an alkaline ionomer (Pention-S72-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio of 5:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Xion-petion-50) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 20 mg of trigonelline was dispersed in 50 mL of aqueous solution to obtain an additive solution. The additive solution was uniformly sprayed onto both catalyst layers. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in a 5 mol / L KOH solution for 48 h. The anion exchange membrane, anode and cathode catalyst layers, and gas diffusion layer (carbon paper, 22BB) after ion exchange together constitute the membrane electrode, denoted as Fe-N-C+trigonelline.

[0110] Example 16

[0111] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0112] 50 mg of Fe-NC catalyst was uniformly mixed with an alkaline ionomer (Pention-S72-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio 1:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Xion-petion-50) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 20 mg of trigonelline derivative (arecoline) was dispersed in 50 mL of aqueous solution to obtain an additive solution. The additive solution was uniformly sprayed onto both catalyst layers. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in a 5 mol / L KOH solution for 48 h. The anion exchange membrane, anode and cathode catalyst layers, and gas diffusion layer (carbon paper, 22BB) after ion exchange together constitute the membrane electrode, denoted as Fe-N-C+arecoline.

[0113] Example 17

[0114] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0115] 50 mg of Fe-NC catalyst was uniformly mixed with an alkaline ionomer (Pention-S72-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio 1:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Xion-petion-50) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 20 mg of trigonelline derivative (1-methyl-3,6-) was added. The additive solution was obtained by dispersing 1-methyl-3,6-dihydro-2H-pyridine-5-carboxylic acid prop-2-ynyl ester in 50 mL of aqueous solution. The additive solution was then uniformly sprayed onto the catalyst layers on both sides. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in 5 mol / L KOH solution for 48 h. The anion exchange membrane after ion exchange, the anode and cathode catalyst layers, and the gas diffusion layer (carbon paper, 22BB) together constitute the membrane electrode, denoted as Fe-N-C+1-methyl-3,6-dihydro-2H-pyridine-5-carboxylic acid prop-2-ynyl ester.

[0116] Example 18

[0117] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0118] 50 mg of Fe-NC catalyst was uniformly mixed with an alkaline ionomer (Pention-S72-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio of 1:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Xion-petion-50) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 20 mg of trigonelline derivative (guanidine ethyl ester) was dispersed in 50 mL of aqueous solution to obtain an additive solution. The additive solution was uniformly sprayed onto both catalyst layers. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in a 5 mol / L KOH solution for 48 h. The anion exchange membrane, anode and cathode catalyst layers, and gas diffusion layer (carbon paper, 22BB) together constitute the membrane electrode, denoted as Fe-N-C+guanidine ethyl ester.

[0119] Example 19

[0120] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0121] 50 mg of Fe-NC catalyst was uniformly mixed with an alkaline ionomer (Pention-S72-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio 1:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Xion-petion-50) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 20 mg of trigonelline derivative (N,N-diethyl-1-methyl) was added. The additive solution was obtained by dispersing 3,6-dihydro-2H-pyridine-5-carboxamide in 50 mL of aqueous solution. The additive solution was then uniformly sprayed onto the catalyst layers on both sides. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in 5 mol / L KOH solution for 48 h. The anion exchange membrane after ion exchange, the anode and cathode catalyst layers, and the gas diffusion layer (carbon paper, 22BB) together constitute the membrane electrode, denoted as Fe-N-C+N,N-diethyl-1-methyl-3,6-dihydro-2H-pyridine-5-carboxamide.

[0122] Example 20

[0123] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0124] 50 mg of Fe-NC catalyst was uniformly mixed with an alkaline ionomer (Pention-S72-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio 1:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Xion-petion-50) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 20 mg of trigonelline derivative (1-methyl-1,2,5,6-tetrahydronicotinic acid ethyl ester) was dispersed in 50 mL of aqueous solution to obtain an additive solution. The additive solution was uniformly sprayed onto both catalyst layers. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in a 5 mol / L KOH solution for 48 h. The anion exchange membrane, anode and cathode catalyst layers, and gas diffusion layer (carbon paper, 22BB) together constitute the membrane electrode, denoted as Fe-N-C+1-methyl-1,2,5,6-tetrahydronicotinic acid ethyl ester.

[0125] Example 21

[0126] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0127] 50 mg of Fe-NC catalyst was uniformly mixed with an alkaline ionomer (Pention-S72-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio 1:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Xion-petion-50) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 20 mg of trigonelline derivative (arecoline) was dispersed in 50 mL of aqueous solution to obtain an additive solution. The additive solution was uniformly sprayed onto both catalyst layers. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in a 5 mol / L KOH solution for 48 h. The anion exchange membrane, anode and cathode catalyst layers, and gas diffusion layer (carbon paper, 22BB) after ion exchange together constitute the membrane electrode, denoted as Fe-N-C+arecoline.

[0128] Example 22

[0129] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0130] 50 mg of Fe-NC catalyst was uniformly mixed with an alkaline ionomer (Pention-S72-5wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio of 1:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Xion-petion-50) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 20 mg of trigonelline derivative (ethyl 1-methyl-4-oxopiridine-3-carboxylate) was dispersed in 50 mL of aqueous solution to obtain an additive solution. The additive solution was uniformly sprayed onto both sides of the catalyst layer. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in a 5 mol / L KOH solution for 48 h. The ion-exchanged anion exchange membrane, the anode and cathode catalyst layers, and the gas diffusion layer (carbon paper, 22BB) together constitute the membrane electrode, denoted as Fe-N-C+1-methyl-4-oxopiridine-3-carboxylate.

[0131] The chemical structural diagrams of trigonelline and its derivatives are shown below. Figure 9 As shown, Figure 10 This is a schematic diagram illustrating the preparation process of the highly water-retaining cathode catalyst layer in Examples 15-22. The membrane electrode assembly is placed into a fuel cell fixture for alkaline fuel cell testing. Hydrogen gas is introduced at the anode and oxygen gas at the cathode. The performance of batteries composed of Fe-NC and Fe-NC-trigonelline is compared and tested. Figure 11 Example 15 demonstrates the significant performance enhancement effect of trigonelline as a high water-retention additive on battery performance, with a marked increase in peak power density of 95 mW / cm³.2 Table 3 compares the degree to which various trigonelline derivatives, as water-retaining agents, improve the output power density of fuel cells.

[0132] Table 3 Performance of fuel cells with different water-retaining agents (trigonelline derivatives)

[0133]

[0134] Example 23

[0135] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0136] 50 mg of FeCo-C catalyst was uniformly mixed with an alkaline ionomer (FAA-3-SOLUT-10, 10 wt%) and dispersed in solvent II of H2O and IPA (H2O to IPA volume ratio 2:1) to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (Sustainion B28-50 Grade T) to form a cathode catalyst layer. A commercial PtRu-C catalyst was sprayed onto the anode side of the alkaline membrane to form an anode catalyst layer. 5 mg of 5,10,1 An additive solution was obtained by dispersing 5,20-tetra(4-trimethylamino)phenylporphyrin tetrabenzenesulfonate in 50 mL of methanol solution. The additive solution was then uniformly sprayed onto the catalyst layers on both sides. The alkaline anion exchange membrane with the catalyst layer was subjected to ion exchange in 1 mol / L KOH solution for 24 h. The anion exchange membrane, the anode and cathode catalyst layers, and the gas diffusion layer (carbon cloth) together constitute the membrane electrode, denoted as FeCo-C+5,10,15,20-tetra(4-trimethylamino)phenylporphyrin tetrabenzenesulfonate.

[0137] The chemical structure diagram of 5,10,15,20-tetra(4-trimethylamino)phenylporphyrin tetramethylbenzenesulfonate is shown below. Figure 12 As shown. The membrane electrode assembly was used in a fuel cell fixture for alkaline fuel cell testing. Hydrogen was introduced at the anode and oxygen at the cathode. The performance of batteries composed of FeCo-C and FeCo-C-5,10,15,20-tetra(4-trimethylamino)phenylporphyrin tetratoluenesulfonate was compared. Figure 13 The study demonstrated that 5,10,15,20-tetra(4-trimethylamino)phenylporphyrin tetrabenzenesulfonate, as a high water-retention additive, significantly improved battery performance, with a peak power density increase of 38 mW / cm². 2 .

[0138] Example 24

[0139] A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity includes the following steps:

[0140] 10 mg of Pt-C catalyst and 10 mg of Fe-NC catalyst were mixed and dispersed together with 20 mg of polyacrylamide in 100 mL of water. The mixture was stirred continuously for 24 h in an N2 atmosphere at 80 °C to obtain a suspension. The suspension was centrifuged and washed with water to obtain an alkaline fuel cell catalyst sample, denoted as Pt-C+Fe-N-C+polyacrylamide. The sample was dried at 60 °C for 24 h.

[0141] The chemical structure diagram of polyacrylamide is shown below. Figure 14 As shown, the obtained catalyst was uniformly mixed with an alkaline ionomer (SustainionXA-9) and dispersed in solvent II of H2O and IPA to obtain a catalyst solution. The catalyst solution was uniformly sprayed onto an alkaline membrane (SustainionB28-50 Grade T) to form the cathode catalyst layer; MoO2 catalyst was sprayed onto the anode side of the alkaline membrane to form the anode catalyst layer; the alkaline anion membrane sprayed with catalyst was subjected to ion exchange in a 1 mol / L KOH solution for 24 h. The ion-exchange anion membrane, the cathode and anode catalyst layers, and the gas diffusion layer (graphite felt) together constitute the membrane electrode assembly (MEA). This MEA was assembled into a fuel cell fixture for alkaline fuel cell testing. Hydrogen gas was introduced into the anode and oxygen gas was introduced into the cathode. The performance of Pt-C+Fe-NC and Pt-C+Fe-NC-polyacrylamide-based batteries was compared and tested. Figure 14 This study demonstrates the performance-enhancing effect of polyacrylamide as a high-water-retention additive on fuel cells, increasing peak power density by 130 mW / cm³. 2 .

[0142] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations. The above-described embodiments are merely preferred embodiments for fully illustrating this invention, and their scope of protection is not limited thereto.

Claims

1. A method for preparing an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity, characterized in that, This includes methods such as direct additive introduction or additive coating. The additive direct introduction method is prepared according to the following steps: the unmodified catalyst and additives are dispersed in solvent I, stirred and mixed at 25-80℃ for 1-72h, and then separated and dried to obtain an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity. The additive coating method is prepared according to the following steps: the unmodified catalyst is mixed evenly with the alkaline ionomer, and then dispersed in solvent II to obtain a catalyst-ionomer dispersion. The catalyst-ionomer dispersion is coated to obtain a catalyst layer. Then, the additive is coated and penetrated into the catalyst layer to obtain an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity. The additive is selected from one or more combinations of tetramethylammonium, tetramethylammonium derivative tetramethylammonium-R, mepiquat chloride, mepiquat chloride derivative mepiquat chloride-R, halmanine, halmanine derivative halmanine-R, trigonelline, trigonelline derivative trigonelline-R, 5,10,15,20-tetra(4-trimethylamino)phenylporphyrin tetratoluenesulfonate, and polyacrylamide. Wherein, R is selected from one or more combinations of methyl, ethyl, propyl, butyl, carboxyl, carbonyl, ether, phenyl, and amino; The derivatives of the tetramethylammonium include tetraethylammonium hydroxide, triethylmethylammonium hydroxide, trimethylphenylammonium hydroxide, N,N,N-trimethyl-1-adamantylammonium hydroxide, and benzyltrimethylammonium hydroxide; the derivatives of the halman base include 1-methyl-9H-pyrido[3,4-b]indole-6-amino, methyl 6-amino-1-methyl-9H-pyrido[3,4-b]indole-3-carboxylic acid, halol, quassin, and 1 -Methyl-1,2,3,4-tetrahydro-β-carboxylic acid; the derivatives of the trigonelline include arecoline, 1-methyl-3,6-dihydro-2H-pyridine-5-carboxylic acid prop-2-ynyl ester, guanidine ethyl ester, N,N-diethyl-1-methyl-3,6-dihydro-2H-pyridine-5-carboxamide, 1-methyl-1,2,5,6-tetrahydronicotinic acid ethyl ester, arecoline, and 1-methyl-4-oxopiridine-3-carboxylic acid ethyl ester.

2. The method for preparing the alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity according to claim 1, characterized in that, In the direct introduction method of the additive, solvent I is selected from water, methanol, ethanol, propanol, isopropanol, ethylene glycol, glycerol, acetone, chloroform, N,N , - One or more of dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the mass ratio of unmodified catalyst to additive is 1:0.01-10; In the additive coating method, the mass ratio of the unmodified catalyst to the basic ionomer is 0.1-10:1; solvent II is H2O, isopropanol, or a mixture of both. The basic ionomer is selected from one of FAA-3-SOLUT-10, FAA-3-EtOH-5, PiperION-A5-HCO3-EtOH, Pention-D35-5wt%, Pention-D18-5wt%, Pention-S72-10wt%, Pention-S72-20wt%, Pention-S72-5wt%, SustainionXA-9, SustainionXB-7XC-1, and SustainionXC-2.

3. The method for preparing the alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity according to claim 1, characterized in that, The unmodified catalyst is selected from one or more combinations of noble metal alloy catalysts, noble metal single-atom catalysts, non-noble metal single-atom catalysts, and non-noble metal alloy catalysts.

4. The method for preparing the alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity according to claim 3, characterized in that, The noble metal alloy catalyst is selected from TKK47% PtCo-C and JM PtRu-C; the noble metal single-atom catalyst is selected from Pt-NC, Pd-NC, and Ir-NC; the non-noble metal single-atom catalyst is selected from Fe-NC, Co-NC, Ni-NC, Mn-NC, FeCo-NC, FeMn-NC, and Fe-Ni-NC; and the non-noble metal alloy catalyst is selected from FeCo-C and FeNi-C.

5. An alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity, prepared by the method according to any one of claims 1-4, characterized in that, It includes an unmodified catalyst and an additive, wherein the unmodified catalyst is an alkaline fuel cell catalyst, and the additive is an organic compound with high water retention and high ion conductivity, and the additive is adsorbed onto the unmodified catalyst.

6. A cathode catalyst layer prepared using the alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity as described in claim 5, characterized in that, Using an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity prepared by the direct introduction of additives as raw material, the cathode catalyst layer is prepared according to the following steps: the alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity is mixed evenly with an alkaline ionomer, and then dispersed in solvent II to obtain a coating liquid. The coating liquid is then uniformly coated onto an alkaline membrane to obtain the cathode catalyst layer. In the additive coating method, the mass ratio of alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity to alkaline ionomer is 0.1-10:1; Using an alkaline fuel cell catalyst containing additives with high water retention and high ion conductivity prepared by an additive coating method as raw material, the cathode catalyst layer is prepared according to the following steps: the unmodified catalyst is mixed evenly with an alkaline ionomer, and then dispersed in solvent II to obtain a catalyst-ionomer dispersion. The catalyst-ionomer dispersion is coated onto an alkaline membrane to obtain a catalyst layer. Then, additives are coated and penetrated into the catalyst layer to obtain an alkaline fuel cell catalyst layer containing additives with high water retention and high ion conductivity. The alkaline membrane is selected from one of the following: Xion-petion-72-15CL-10, Xion-petion-72-5CL-10, Xion-petion-20, Xion-petion-30, Xion-petion-50, PiperION-A15R-HC03, PiperION-A20R-HC03, PiperION-A40R-HC03, FAA-3-20, FAA-3-50, FAA-3-PE-30, FAA-3-PK-75, Sustainion B28-50 Grade T, Sustainion X37-50 Grade 60, W-25, and W-15.

7. The application of the cathode catalyst layer according to claim 6 in the preparation of an alkaline fuel cell, characterized in that, The alkaline fuel cell is prepared according to the following steps: An anode catalyst is coated on the anode side of an alkaline membrane coated with a cathode catalyst layer to form an anode catalyst layer. The alkaline membrane containing the cathode catalyst layer and the anode catalyst layer undergoes ion exchange in a KOH solution. The ion-exchanged alkaline membrane and the gas diffusion layer are then used together to form a membrane electrode assembly. The membrane electrode assembly is assembled into a fuel cell fixture, and hydrogen gas is introduced into the anode and oxygen gas is introduced into the cathode.

8. The application of the cathode catalyst layer according to claim 7 in the preparation of alkaline fuel cells, characterized in that, The anode catalyst layer is also coated with additives. Anode catalysts include one or more combinations of noble metal catalysts, non-noble metal catalysts, and metal oxide catalysts; The gas diffusion layer is selected from one of carbon paper, carbon cloth, and graphite felt; The concentration of KOH solution is 0.1-10 mol / L, and the ion exchange time is 3-150 h.

Citation Information

Patent Citations

  • Preparation method of fuel cell membrane electrode slurry

    CN109390593A